ANALISIS OPTIMALISASI DANA PERIMBANGAN DESA MELALUI INTERVENSI KEUANGAN SYARIAH UNTUK PARA NELAYAN - Sayid Salahuddin Alaydrus; Fatiya Rumi Humaira; Anisa Humairoh (STES Islamic Village, 2019)
Dana Perimbangan Desa (DPD) is a fundallocated to boost economic growth and empowerment of rural areas in Indonesia. The objective of DPD is to achieve better equality between rural and urban area in Indonesia. On the other hand, in rural area, a lot of Small Medium Entrepreunerhips (SMEs) are facing financial difficulties to be able to grow and need certain support of capital and funding, especially in fishing villages. In many fishing village there are a lot of number of fishermen is still have low income and they are still suffering from poverty. The present of DPD brings new hope of SMEs in many village, particularly in fishing villages. This research to investigate the role of DPD in order to optimalize the income of fishermen as well as to know what the role of IslamicMicrofinance Institutions (IMFIs) or LKMS to solve the problem of fishhermen who facing the lack of capital using the Islamic schema of financing. The findings of this study are: the scheme of funding will provide a “money pockets” for the fishermen: one for daily consumptions, one for productions capital, one for longer planned financial necessity, and one for investment. The scheme is especially designed to educate financial allocation management for the fishermen so that they can manage their money not only for short-term period but also for the long-term period. The educating objective came from the value of IMFIs itselves that prioritize MFI to grow together with the SMEs by giving mentorship, unlike the conventional MFI that only cares for financial return.